Business Ethics In Digital Trading Transactions Buy Now Pay Later (BNPL) From An Islamic Sharia Perspective - Kusumorini, Fenti; Subaidi, Subaidi; Afiyanti, Dina (Yayasan Pendidikan Islam (YPI) AN NUR INSANI, 2025)
Buy Now Pay Later (BNPL) digital financial services have become a global phenomenon, offering ease of transaction by deferring payment. In the context of Islamic economics, this practice has sparked legal (fiqh) debate regarding its compatibility with Islamic principles, particularly the prohibition of riba (usury), gharar (uncertainty), and maysir (gambling). This article aims to analyze conventional BNPL schemes from an Islamic Sharia perspective, identify elements that potentially violate Islamic law, and offer alternative models based on Sharia contracts, such as Murabahah or Bai' Muajjal (deferred sale). The results of the study show that conventional BNPL that charges interest, percentage fees, or late fees that are ribawi in nature are generally contrary to Sharia. The implementation of Sharia-compliant BNPL must be based on a transparent sale and purchase contract, free from usury, and upholding the value of justice ('adl) and avoiding excessive consumption (israf).